The Impact of Remitances on Albanian GDP and Economic Growth - Myftari, Enea (Mediterranean Journal of Social Sciences, 2012)
This paper includes a considerable part of Albania's macroeconomic, focusing mostly on remittances framework. The purposeof this paper is to show through conducted analysis, the reality of remittances in Albania. These remittances have been evaluated fromtheir beginning up to now, by seeing consequences that brought these remittances, and focusing on the level they represent in Albania'sGDP. This paper begins with a historical overview of the factors that led to the start of remittances to Albania, and continues withanalyzing of remittances effect on the economy of Albania. The distribution of remittances in Albania is been presented according todifferent urban and rural areas. The changes in remittances inflow are illustrated among years, and the paper focuses on the role ofremittances especially on its share in Albania’s GDP. This paper includes also graphics and their valuable interpretation. Themethodology which is used in this paper is, obtaining information from various sources and literature. The facts and analysis on the topichas been adapted by highlighting my personal ideas on the matter. Based on the information regarding this paper, it can be concludedthat remittance inflows constitute a very important share in GDP and economic development of Albania. Lastly, a recomendation toAlbanian government would be that, these remittances which in many cases are used mostly for consumption, must be oriented towardsinvestment.